2021
DOI: 10.1016/j.jallcom.2020.158315
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous synthesis of highly luminescent ternary alloyed Mn-doped ZnSeS quantum dots capped with 2-mercaptopropionic acid

Abstract: Highly photoluminescent and water dispersible ternary alloyed Mn-doped ZnSeS and core/shell Mn:ZnSeS/ZnS quantum dots (QDs) with pure dopant emission were synthesized through a simple aqueous route using thiolactic acid (2-MPA) as a capping ligand.Transmission electron microscopy and X-ray diffraction show that Mn:ZnSeS nanocrystals are of spherical shape, with a diameter of 2.4 nm and a cubic zinc blende structure. With the overcoating of the ZnS shell, the particle size increases to 3.7 nm, which confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…When the ratio of Se : Zn exceeds 0.9, the PL spectra present a remarkable change as two different peaks appear: one, located at ∼380 nm, originates from the heterogeneity of the Se-rich surface states and relaxation of the vibrational states between the electronic excited and ground states, 38 and the other is the Mn 2+ emission at ∼580 nm from the 4 T 1 -6 A 1 transition. 39,40 Significantly, the PL intensity enhancement of the Mn 2+ transition with the increasing Se content illustrates that Se-rich content contributes to the Mn 2+ doping. Suffering from the lattice self-purification effect, 41 the doping of Mn 2+ into the ZnSe lattice will be inhibited in small QDs.…”
Section: Development Of Znse:mn Based Qds With Different Surface Stoi...mentioning
confidence: 95%
“…When the ratio of Se : Zn exceeds 0.9, the PL spectra present a remarkable change as two different peaks appear: one, located at ∼380 nm, originates from the heterogeneity of the Se-rich surface states and relaxation of the vibrational states between the electronic excited and ground states, 38 and the other is the Mn 2+ emission at ∼580 nm from the 4 T 1 -6 A 1 transition. 39,40 Significantly, the PL intensity enhancement of the Mn 2+ transition with the increasing Se content illustrates that Se-rich content contributes to the Mn 2+ doping. Suffering from the lattice self-purification effect, 41 the doping of Mn 2+ into the ZnSe lattice will be inhibited in small QDs.…”
Section: Development Of Znse:mn Based Qds With Different Surface Stoi...mentioning
confidence: 95%
“…[12] Mabrouk et al synthesized 2-MPA-capped Mn:ZnSeS and Mn:ZnSeS/ZnS QDs, which possessed high quantum efficiency and photostability. [13] Chen et al synthesized quaternary/ternary alloyed CdZnSeS/ZnSeS QDs with excellent luminescence performance and thermal stability. [14] However, the DOI: 10.1002/ppsc.202300101 photoelectric properties of ZnSSe particles are limited due to their high surface energy, easy agglomeration of particles, and fast electron-hole pair recombination rate, which is similar to that of ZnS and ZnSe.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Cudoping of ZnS and ZnSe QDs has been investigated and it was demonstrated that the relaxation of the exciton occurs via the t2 energy states of Cu 2+ resulting in an emission in the green region valuable for applications such as bio-imaging, sensing, photocatalysis and light emitting devices [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Gradient alloyed ZnSeS QDs are well-known to exhibit improved optical properties and higher stability compared to binary ZnS or ZnSe QDs [49][50][51][52][53] but their doping with Cu has only scarcely been investigated [54,55]. Core/shell Cu-doped ZnSeS/ZnS QDs were prepared using the nucleation-doping method in which the Cu dopant is introduced at the earlier stage of the synthesis and thus located in the ZnSeS core [54,55].…”
Section: Introductionmentioning
confidence: 99%